Figurate number (arithmetic prigression) and electromagnetic Wave scattering on spatial lattices of resonant magnetodielectric spheres - Kozar, A. I. (Begell House, 2003)
Considered is the problem of electromagnetic wave scattering on complex spatial lattices of special kind, consisting of resonant-size spheres whose spatial distribution is controlled by figurate numbers. Expressions for the scattered fields are derived.
Keywords: resonanat magnetodielectric spheres